Effect of nutritional status on arsenic and smokeless tobacco induced genotoxicity, sperm abnormality and oxidative stress in mice in vivo. (22nd March 2018) - Das, Samrat; Langthasa, Pimily; Barhoi, Dharmeswar; Upadhaya, Puja; Giri, Sarbani
Abstract : Background : Recently, high concentrations of arsenic have been documented in ground waters of Southern Assam, India. Indiscriminate smokeless tobacco consumption is a common practice in this region. Correlation between nutritional status and arsenic and smokeless tobacco‐induced health effects has not been taken up in humans or other test systems. Methods : Mice were divided into groups based on protein (casein) content in the diet: High protein (40%), optimum protein (20%), and low protein (5%). Simultaneous chronic exposure (90 days) to arsenic and smokeless tobacco ( sadagura ) orally was given to evaluate the extent of the cytological and genotoxicological damage. Micronucleus assay and Comet assay of the femur bone marrow cells were conducted. Germ cell toxicity was evaluated by recording the sperm head abnormalities and total sperm count. Cell cycle analysis was performed in femur bone marrow cells using flow cytometer. Hepatic, renal, and intestinal tissues were analyzed for various oxidative stress evaluations. Histological examination of liver and kidney was performed. Results : Notably, high protein diet groups had lower arsenic and sadagura induced genotoxicity, germ cell abnormalities and oxidative stress as compared to optimum protein and low protein diet counterparts. Conclusion : Our study indicates that sufficient levels of dietary protein appear to reduce the long‐term arsenic and smokeless tobacco‐induced toxicity in mice test system, as compared to lower or deficient amount of protein in the diet. This observation has implications and invites further studies especially epidemiological studies in the human population exposed to arsenic in South East Asian countries. Environ. Mol. Mutagen. 59:386–400, 2018. © 2018 Wiley Periodicals, Inc.